2021
DOI: 10.1038/s41467-021-20954-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photoelectric effect in halide perovskites for regenerative electron sources

Abstract: Electron sources are a critical component in a wide range of applications such as electron-beam accelerator facilities, photomultipliers, and image intensifiers for night vision. We report efficient, regenerative and low-cost electron sources based on solution-processed halide perovskites thin films when they are excited with light with energy equal to or above their bandgap. We measure a quantum efficiency up to 2.2% and a lifetime of more than 25 h. Importantly, even after degradation, the electron emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…However, once a Cs coating is added, systems containing I and terminated with a [001] surface have the lowest work functions. These results are in good agreement with the recent experimental demonstration of Cs-coated perovskite materials as photocathode devices, 37 and the insights gained here can further be used for material development. A phenomenological model was developed to predict the work function with the material, surface coverage, and surface termination.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, once a Cs coating is added, systems containing I and terminated with a [001] surface have the lowest work functions. These results are in good agreement with the recent experimental demonstration of Cs-coated perovskite materials as photocathode devices, 37 and the insights gained here can further be used for material development. A phenomenological model was developed to predict the work function with the material, surface coverage, and surface termination.…”
supporting
confidence: 91%
“…In order to lower the work function into the optical region for more affordable operating conditions, one technique is to add a coating of Cs. Indeed, recently reported efficient free-electron emission halide perovskite thin films operating in the visible to the ultraviolet spectral range for the first time further motivate in-depth computational studies on this emergent application.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Coating perovskite surfaces with a metal like Cs presents potential technological promises in applications requiring electron sources such as electron beam accelerator facilites. 28 It has recently been demonstrated that by depositing monolayers of Cs on top of halide perovskites, the electron emission efficiency was improved 29 and the improvement was attributed to a change of sign of the electron affinity, which translates into a diminishing work function. 1).…”
Section: Effect Of the Surface Coating With Csmentioning
confidence: 99%
“…The photoelectric effect 1 describes the response of molecules and materials to electromagnetic radiation by emission of electrons. This effect plays a fundamental role in daily life, but also in cutting-edge technology, such as optoelectronic devices, 2,3 regenerative electron sources for free-electron lasers, 4 or photovoltaics, for instance to design artificial ion pumps that mimic nature. 5 …”
Section: Introductionmentioning
confidence: 99%